Malawi Stories: mapping an art-science collaborative process. Issue 3 (20th November 2019) - Nicholson, Philip J.; Dixon, Deborah; Pullanikkatil, Deepa; Moyo, Boyson; Long, Hazel; Barrett, Brian
ABSTRACT: This paper outlines a project drawing together an artist working on creative GIS, a geomatics scholar, an NGO leader, a rural geographer and soil scientist, an environmental geochemist, and a political geographer. With a shared interest in the social and physical processes affecting people's lives in Malawi, and the possibilities for interdisciplinary collaboration, the team engaged in practice-based mapping of our data sources and respective methodologies. The project relates to two sites in Malawi: Tikondwe Freedom Gardens and the Likangala River. The paper details our practices as we shared, debated, and repurposed our data as a means of situating these practices and data. Using paper and pen, whiteboard, PowerPoint, and web-design software, we note here our effort to map a 'space of experimentation' highlighting, and reflecting on, our diverse disciplinary orientations, training, instrumentation, recording, and reporting procedures, as well as bodily practices that enable and give animation to these factors.